20th International Scientific Conference Engineering for Rural Development Proceedings 2021
DOI: 10.22616/erdev.2021.20.tf197
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing enzymaticaly treated hay substrate biomethane potential using biodegradable surfactants

Abstract: Second-generation biofuel production from grassland biomass is getting more and more popular as a research topic. A zero-to-low waste production strategy is one of the core ideas in the technology design. Biogas production from lignocellulose is one of the promising components in technology development, which can solve the upcoming remaining lignocellulose problems. This study is looking into lignocellulose leftovers after sugar extraction as a substrate for anaerobic digestion enhancing the fermentation proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Traces of the BHW substrate toxic effect is also present in the sludge and co-digestion system, because the 30-day BMP value for 2.5% BHW addition Anionic surfactant positive effect on the AD process cannot be directly linked to the HES amount added to the system, since MPWW DAF sludge contains around 82% HES from the total VS, while DWW DAF sludge only contains around 18% of (Figure 2). This positive effect has also been detected in the preliminary studies where the same surfactant showed a favourable effect for the BHW substrate AD [55]. Although the BMP values were detected in different experimental set-ups, there is a clear beneficial influence on the addition of a biodegradable anionic surfactant to the AD.…”
Section: Bhw and Fog-containing Primary Sludge Co-digestion With Sas ...supporting
confidence: 65%
See 4 more Smart Citations
“…Traces of the BHW substrate toxic effect is also present in the sludge and co-digestion system, because the 30-day BMP value for 2.5% BHW addition Anionic surfactant positive effect on the AD process cannot be directly linked to the HES amount added to the system, since MPWW DAF sludge contains around 82% HES from the total VS, while DWW DAF sludge only contains around 18% of (Figure 2). This positive effect has also been detected in the preliminary studies where the same surfactant showed a favourable effect for the BHW substrate AD [55]. Although the BMP values were detected in different experimental set-ups, there is a clear beneficial influence on the addition of a biodegradable anionic surfactant to the AD.…”
Section: Bhw and Fog-containing Primary Sludge Co-digestion With Sas ...supporting
confidence: 65%
“…Digestion with a 2.5% load has a higher AD velocity and, on average, 5-15% more BMP is obtained from day 3 to day 25 in comparison to the 5% sample. Although the 30-day average BMP value for both samples reach the same value of 549 mLCH 4 /gVS, studies with activated sludge digestate as the inoculum and 2.5% BHW demonstrated significantly lower biomethane potential-378 mLCH 4 /gVS [55]. It is probably the more adapted bacterial consortia in the agricultural digestate containing a higher amount of Acetoanaerobium spp.…”
Section: Selected Substrate Bmp and Organic Loadingmentioning
confidence: 85%
See 3 more Smart Citations